2021
DOI: 10.1111/liv.15106
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Delta virus in migrants: The challenge of elimination (ANRS CO22 HEPATHER cohort)

Abstract: Novel treatments for hepatitis Delta virus (HDV) infection provide promising opportunities to treat patients with hepatitis B virus (HBV) and HDV co-infection. However, current clinical trials on HDV treatment rarely explore patients' barriers to treatments. In Europe, HDV infection mostly affects young migrants from HDV-endemic areas who experience early liver-related mortality. Migrants are more likely to face multiple situations of statutory and socioeconomic insecurity and structural barriers than non-migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This subject has become increasingly relevant in Europe in recent years as domestic infection, mostly related to intravenous drug use, are being replaced by cases introduced by immigration from endemic areas [3]. Also, the difficulties that we faced in bringing our patient to clinic and starting treatment are in line with reports from the French cohort, where migrant populations were shown to have suboptimal adherence and commitment to care, driven by socioeconomic insecurity [27].…”
Section: Discussionmentioning
confidence: 82%
“…This subject has become increasingly relevant in Europe in recent years as domestic infection, mostly related to intravenous drug use, are being replaced by cases introduced by immigration from endemic areas [3]. Also, the difficulties that we faced in bringing our patient to clinic and starting treatment are in line with reports from the French cohort, where migrant populations were shown to have suboptimal adherence and commitment to care, driven by socioeconomic insecurity [27].…”
Section: Discussionmentioning
confidence: 82%
“…33 HBV and HDV prevention campaigns in Europe are almost non-existent for migrants. 34 Despite constituting the major burden of HDV, this at-risk group is the most marginalized and neglected. Their obstacles push them to give less importance to their disease, which propagates misperceptions about severity of viral hepatitis, causes delays in treatment initiation and weakens their commitment and adherence to care.…”
Section: At-risk Groupsmentioning
confidence: 99%
“…A plethora of factors affect migrants' free access to healthcare such as socioeconomic insecurity, lack of social rights, language barriers, housing insecurity, unexpected expenditures and difficulties 33 . HBV and HDV prevention campaigns in Europe are almost non‐existent for migrants 34 . Despite constituting the major burden of HDV, this at‐risk group is the most marginalized and neglected.…”
Section: Endemic Versus Non‐endemic Countries—recognizing Differences...mentioning
confidence: 99%
“…In high‐income countries, in contrast, the epidemiology has shifted from people in older age groups to younger persons, often migrants from countries where HDV infection is endemic. Recent studies performed in France showed that 86% of cases of hepatitis D occurred in migrants 10 . Diagnosis of HDV infection requires the determination of HDV RNA, but the US Food and Drug Administration (FDA), for instance, has no approved assay for HDV RNA or for anti‐HDV antibodies.…”
mentioning
confidence: 99%
“…Recent studies performed in France showed that 86% of cases of hepatitis D occurred in migrants. 10 Diagnosis of HDV infection requires the determination of HDV RNA, but the US Food and Drug Administration (FDA), for instance, has no approved assay for HDV RNA or for anti-HDV antibodies. HDV diagnostics are not included in WHO’s list of essential diagnostics.…”
mentioning
confidence: 99%